Enhanced Indoor Air Quality Protection Standards in USA, EU, Japan and Their Applicability in Korea - Seung-Jung Lee; Sang-Hun Park; Seong-Ku Yeo; Seong-Cheon Kim (대한환경공학회지)
This study analyzes the trends in enhanced indoor air quality protection standards in the United States, EU, and Japan to explore potential improvements and applicability for Korea's indoor air quality management policies. The study compared and analyzed each country’s policy objectives, management targets, standards, implementation strategies, and legal frameworks, with particular focus on the U.S.’s customized guidelines, EU’s integrated strategy, and Japan’s building material system. WHO has strengthened its PM2.5 standards, while the U.S. implements customized guidelines and high-efficiency filters, the EU maintains integrated management of energy efficiency and air quality, and Japan implements a building material rating system and 24-hour ventilation system. In contrast, while Korea has established legal frameworks, its management scope is limited, standards remain below international recommendations, and inter-ministerial cooperation is insufficient. Therefore, this study proposes the gradual introduction of WHO standards, implementation of a building material rating system, strengthening inter-ministerial cooperation, and establishment of real-time monitoring systems, with particular emphasis on managing facilities used by vulnerable populations.